(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This study is devoted to the analysis of the empirical base available today, which can form the basis of analytical models describing the patterns, causes and markers of such a dangerous phenomenon as human trafficking. In the course of the study, we found contradictions in the available sources, and also identified a number of difficulties generated by the specifics of the available data: inaccuracies, omissions, noise, distortions caused by flaws in the methodology or the use of unfounded expert assessments instead of factual material. Nevertheless, the analysis showed that even today, on the available empirical base, it is possible to identify reliable statistically significant regularities. At the same time, as an assessment of the level of trafficking, it is advisable to rely on the statistics of international organizations, while the international statistics of NGOs is contradictory and needs improvement.